2014
DOI: 10.1016/j.ygyno.2014.03.225
|View full text |Cite
|
Sign up to set email alerts
|

Use and duration of chemotherapy and its impact on survival in early-stage ovarian cancer

Abstract: Objective-Although 5-year survival for early-stage ovarian cancer is favorable, prognosis at recurrence is poor, necessitating appropriate initial management. We examined the patterns of care and the impact of the duration of chemotherapy on survival for women with early-stage ovarian cancer.Methods-We used the SEER-Medicare database to identify women ≥65 years of age with stage I ovarian cancer diagnosed from 1992-2009. Patients were categorized as low-risk (non-clear cell histology, stage IA or IB, grade 1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Our results confirmed that chemotherapy did not significantly improve the survival of patients with grade I IA and IB (p = 0.452, HR: 1.547, 95% CI: (0.497-4.815) (Tables 3,4, Fig. 3A), which was consistent with the NCCN Guidelines and previous literature [10,[12][13][14][15].…”
Section: Impact Of Chemotherapy On Survivalsupporting
confidence: 91%
“…Our results confirmed that chemotherapy did not significantly improve the survival of patients with grade I IA and IB (p = 0.452, HR: 1.547, 95% CI: (0.497-4.815) (Tables 3,4, Fig. 3A), which was consistent with the NCCN Guidelines and previous literature [10,[12][13][14][15].…”
Section: Impact Of Chemotherapy On Survivalsupporting
confidence: 91%
“…This is because the duration of chemotherapy does not always determine the number of chemotherapy cycles a patient undergoes, so it cannot be used as a determinant of the type of therapy that the previous survivor received. 9 However, in this study there is a significant association between type of therapy and quality of life in ovarian cancer survivors. Compared to Bughwandass, the types of therapy underwent by the survivors affect their quality of life.…”
Section: Discussionmentioning
confidence: 56%
“…This could affect their attitude to the disease and its treatment. 9 The results obtained for the symptom scale in table 4 also have a fairly low average score (16.91) which shows that the level of symptoms or problems experienced by survivors based on EORTC QLQ OV-28 is not too problematic. This can be seen in abdominal/GI symptoms, other chemotherapy side effects, and hair loss showing very low scores which proves that most survivors no longer experience these complaints that may be experienced during therapy.…”
Section: Resultsmentioning
confidence: 90%
“…A randomized GOG trial comparing three versus six cycles of adjuvant chemotherapy showed no survival benefit for extended chemotherapy despite this strategy being accompanied by increased toxicity 31 . The study conducted by Dinkelspiel et al also reported that extended chemotherapy does not affect survival in the early stage with high risk (HR 0.93, 95% CI 0.67-1.27) 32 . Among 19 patients with FIGO stage IC in our study cohort, 18 had adjuvant chemotherapy and only one did not receive adjuvant treatment.…”
Section: Discussionmentioning
confidence: 93%